TASK-1 channel blockade by AVE1231 increases vasocontractile responses and BP in 1- to 2-week-old but not adult rats - Shvetsova, Anastasia A.; Gaynullina, Dina K.; Schmidt, Nadine; Bugert, Peter; Lukoshkova, Elena V.; Tarasova, Olga S.; Schubert, Rudolf (British journal of pharmacology, 2020)
Background and Purpose The vasomotor role of K2P potassium channels during early postnatal development has never been investigated. We tested the hypothesis that TASK-1 channel (K2P family member) contribution to arterial vascular tone and BP is higher in the early postnatal period than in adulthood. Experimental Approach We studied 10- to 15-day-old (“young”) and 2- to 3-month-old (“adult”) male rats performing digital PCR (dPCR) (using endothelium-intact saphenous arteries), isometric myography, sharp microelectrode technique, quantitative PCR (qPCR) and Western blotting (using endothelium-denuded saphenous arteries), and arterial pressure measurements under urethane anaesthesia. Key Results We found mRNA of Kcnk1-Kcnk7, Kcnk12, and Kcnk13 genes to be expressed in rat saphenous artery, and Kcnk3 (TASK-1) and Kcnk6 (TWIK-2) were most abundant in both age groups. The TASK-1 channel blocker AVE1231 (1 μmol·L−1) prominently depolarized arterial smooth muscle and increased basal tone level and contractile responses to methoxamine of arteries from young rats but had almost no effect in adult rats. The level of TASK-1 mRNA and protein expression was higher in arteries from young compared with adult rats. Importantly, intravenous administration of AVE1231 (4 mg·kg−1) had no effect on mean arterial pressure in adult rats but prominently raised it in young rats. Conclusion and Implications We showed that TASK-1 channels are important for negative feedback regulation of vasocontraction in young but not adult rats. The influence of TASK-1 channels most likely contributes to low BP level at perinatal age.
First published: 29 August 2020
Gesehen am 19.01.2022